2006
DOI: 10.1038/sj.cgt.7700958
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inhibition of tumor growth by soluble Flk-1 gene therapy combined with cisplatin

Abstract: Soluble Flk-1, a soluble vascular endothelial growth factor (VEGF) receptor, is a potent inhibitor of angiogenesis, which could restrain growth and metastasis of some experimental tumors. However, antiangiogenic agents alone cannot eradicate tumor completely, and should be combined with other therapy to enhance their effects. In this study, we evaluated the antitumor activity of the combination therapy in the immunocompetent BALB/c mice bearing H22 hepatoma and Meth A fibrosarcoma, respectively. Mice were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…To conform the role of FPR1 in HCC progression by in vivo experiments using murine cancer cell lines in immunocompetent mice, we examined the effect of FPR1 tumorigenicity in H22 tumor model of BALB/c mice following the method described by another group. 26 We show that FPR1-shRNA had similar antitumor effects in immunocompetent mice shown in immunocompromised mice with human cell line (Fig. S6A, B and C).…”
Section: Fpr1 Knockdown By Shrna Reduces the Tumorigenicity Of Hepatimentioning
confidence: 71%
“…To conform the role of FPR1 in HCC progression by in vivo experiments using murine cancer cell lines in immunocompetent mice, we examined the effect of FPR1 tumorigenicity in H22 tumor model of BALB/c mice following the method described by another group. 26 We show that FPR1-shRNA had similar antitumor effects in immunocompetent mice shown in immunocompromised mice with human cell line (Fig. S6A, B and C).…”
Section: Fpr1 Knockdown By Shrna Reduces the Tumorigenicity Of Hepatimentioning
confidence: 71%
“…The soluble forms of the VEGF receptors bind to the ligand and block their angiogenic action (Kaczmarek et al, 2005). Cancer therapy studies have shown that an increase in the expression of sVEGFR1 (Owen et al, 2012) or sVEGFR2 (Wang et al, 2006;Szentirmai et al, 2008) reduce tumour cell proliferation and increase apoptosis (Szentirmai et al, 2008), which is associated with a reduction in blood flow to the tumour tissues. In the present study, mRNA expression of VEGFR2 on days 4 and 6 (CL formation) of the cycle was at least eightfold higher than that Figure 2 Changes in the ratio of mRNA expression for angiogenic (VEGF120a, VEGFR1 and VEGFR2) and antiangiogenic (VEGF120b, sVEGFR1 and sVEGFR2) VEGF system components in the corpus luteum during the oestrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sKDR can bind with VEGF and compete with normal VEGFR-2 and can function as dominant negative by forming inactive heterodimers with membrane-spanning VEGF receptors [12,38]. To date, many studies have proven that the specific binding of sKDR with VEGF could significantly inhibit the blood vessel formation in tumor tissue, thereby inhibiting the growth, proliferation and migration of tumor [15,23,31,38]. …”
Section: Discussionmentioning
confidence: 99%
“…The soluble kinase insert domain receptor (sKDR) is a soluble form of the extramembrane part of VEGFR2 [14]. It has the same high affinity for VEGF but does not induce angiogenesis [15]. Thus, the delivery of sKDR to tumor tissues inhibits the formation of new blood vessels in the tumor tissues and has an anti-tumor effect [6,16].…”
Section: Introductionmentioning
confidence: 99%